Repurchase Intention Model Development Mediated by Brand Image: A Study at Fore Coffee in Yogyakarta - Nabiela, Ibriza; Wisnalmawati, Wisnalmawati; Religia, Yoga (CV. Strata Persada Academia, 2025)
This study aims to develop a repurchase intention model mediated by brand image, using Fore Coffee consumers in Yogyakarta as the research context. The research is motivated by the rapid growth of social media as a digital marketing strategy and the expansion of the F&B industry, with Fore Coffee successfully integrating digital technology to reach a broader market. A quantitative approach with a descriptive research design was applied. A total of 100 respondents were selected using accidental sampling. Data were analyzed using Structural Equation Modeling (SEM) with the Partial Least Squares (SmartPLS) method. The findings indicate that Social Media Marketing has a positive and significant effect on repurchase intention and brand image. Furthermore, brand image positively and significantly influences repurchase intention. Notably, brand image mediates the relationship between Social Media Marketing and repurchase intention, implying both direct and indirect effects of digital marketing on consumer behavior. These findings highlight the strategic importance of social media in strengthening brand image to foster customer loyalty. The study also suggests that future research should incorporate additional variables such as customer satisfaction, consumer trust, or product quality to further enhance the predictive model of repurchase intention in the coffee or local beverage industry.